Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/cs501874v
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation/Hydrolytic Ring Opening of 5-HMF by Cp*-Iridium(III) Half-Sandwich Complexes for Bioketones Synthesis

Abstract: A new method for one-step synthesis of ketones from biobased 5-hydroxymethylfurfural (5-HMF) and its derivatives is reported. Bipyridine coordinated Cp*-Iridium(III) complexes (Cp*, 1,2,3,4,5-pentamethylcyclopenta-1,3-diene) exhibit highly efficient catalytic performance for hydrogenation/hydrolytic ring opening of 5-HMF and derivatives to produce ketones. The catalytic mechanism is proposed to proceed via carbonyl hydrogenation, hydroxyl group promoted and directed hydrolytic furan ring opening, followed by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
61
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 44 publications
(50 reference statements)
7
61
0
2
Order By: Relevance
“…According to this result, we think that 5‐methylfurfuryl alcohol is the intermediate between 5‐methylfurfural and hexane‐2,5‐dione. In the recent work of Zhang and co‐workers, similar results were observed with the Cp*‐iridium(III) complex. It was suggested that the presence of a hydroxyl group promotes the hydrolysis of the furan ring.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…According to this result, we think that 5‐methylfurfuryl alcohol is the intermediate between 5‐methylfurfural and hexane‐2,5‐dione. In the recent work of Zhang and co‐workers, similar results were observed with the Cp*‐iridium(III) complex. It was suggested that the presence of a hydroxyl group promotes the hydrolysis of the furan ring.…”
Section: Resultssupporting
confidence: 74%
“…(Route 2 in Scheme ), 2A was prepared by acid‐catalyzed hydrolysis of 4‐(5‐methyl‐a‐furyl)‐2‐butanone ( 2D ) from the hydrogenation of the aldol‐condensation product ( 1D ) of methylfurfural and acetone. In the recent work of Zhang and co‐workers, a new method (Route 3 in Scheme ) was developed for the synthesis of 2A through aqueous‐phase hydrogenation of 1A catalyzed by bipyridine‐coordinated Cp*‐iridium(III) complexes (Cp*=1,2,3,4,5‐pentamethylcyclopenta‐1,3‐diene). Compared with the previous two routes, this new route is environmentally friendly and contains fewer steps.…”
Section: Resultsmentioning
confidence: 99%
“…34 However, 14 Kegnaes et al studied the conversion of 5-HMF using O 2 with 2.5 bar pressure in the 15 presence of Ru(OH) x /Al 2 O 3 catalyst, achieved 25% LA at 140 °C. 51 Above results inferred that so far the hydrogenation/ring opening of furans 19 were acquired under strident reaction conditions like usage of H 2 gas with high pressure 20 and high temperature. 51 Above results inferred that so far the hydrogenation/ring opening of furans 19 were acquired under strident reaction conditions like usage of H 2 gas with high pressure 20 and high temperature.…”
mentioning
confidence: 87%
“…There were several reports on the conversion of HMF to HHD. Supported Pd, Pt and Au catalysts were proved to be effective for this conversion . Mentech and their group reported this conversion with 60% yield of HHD using Pt/C by the addition of oxalic acid for the first time .…”
Section: Introductionmentioning
confidence: 99%